PENGGUNAAN SMARTPHONE PADA SISWA SDN 014 SUNGAI PUTIH KECAMATAN TAPUNG KABUPATEN KAMPAR: Penggunaan Smartphone pada Siswa Sdn 014 Sungai Putih Kecamatan Tapung Kabupaten Kampar - Nofri Hasrianto Nofri; Nurvi Susanti; Uswatun Khasanah; Yessi Harnani (Jurnal Kesehatan Komunitas, 2020)
The initial survey and the interview with researchers from 20 students, the children who use smartphones are: 15 students and 5 students do not have a smartphone, the children of 3-5 years have 1 hour per day and 2 hours per day for 6 -18 years. This causes children to be lazy to write and read. This study aims to determine the behavior of smartphone use in SDN 014 Sungai Putih District Tapung District Kampar Regency. This type of research is quantitative research with transversal design. The population of this study was made up of students from SDN 014 Sungai Putih, Tapung district, Kampar Regency. The sample in the study was 157 people. Probability Sampling technique using stratified random sampling. The analysis used univariate and bivariate with chi-square tests, a questionnaire measurement tool. The bivariate analysis results have a significant relationship between knowledge, attitudes, peer influence and family environment. Considering that there is no meaningful relationship, i.e. parental supervision over smartphone usage behavior. Conclusions The family environment is very active in modeling the character of children, including the use of smartphones, it also proves to be able to effectively influence the social interaction of children with their immediate environment. Keywords : knowledge, atude, peers, family environment, smartphone